Beyond mere respect: new perspectives on dignity for healthcare workplace learning - Klinner, Christiane; Dario, Amabile Borges; Bell, Amani; Nisbet, Gillian; Penman, Merrolee; Monrouxe, Lynn V. (Frontiers in Medicine, 2024)
Introduction Although dignity in workplace learning in healthcare is gathering interest, we know little about stakeholders’ conceptualizations in this area across professional groups. Dignity breaches in workplace learning are common, often with serious and long-lasting consequences for the affected. Conceptualizations shape behaviours and experiences. To prevent dignity violations in students’ learning, it is thus important to understand stakeholders’ understandings of the topic. This study therefore explores the dignity conceptualizations around workplace learning that students, placement educators and university staff hold across seven allied health professional groups. Methods Using a social constructionist perspective, we conducted individual and group narrative interviews (n = 51) with students, placement educators and university workplace learning staff from seven allied health professional groups. We used the 5-step Framework Analysis to explore and develop themes, identifying differences and similarities across stakeholder groups. Results We identified eight distinct, yet interrelated, dimensions of dignity from participants’ narratives: dignity as respect, dignity as self-x (the various relationships we have with ourselves), dignity as feeling safe, dignity as understanding otherness, dignity as supporting others, dignity as equality, dignity as professionalism, and dignity as belonging. Dignity as respect was identified across all participants, although mutual respect and a culture of respect were only present in academic participants’ talk. The remaining seven dimensions all present important factors extending our understanding of the construct of dignity. Discussion In line with existing research, our study identifies the absence of an unambiguous, positive conceptualization of dignity in workplace learning among stakeholders. It adds novelty in two ways: by identifying dignity dimensions that require informed action beyond respecting others, and by revealing a tension between dignity as professionalism and dignity as equality. We suggest revising existing dignity concepts in workplace learning to address this tension and to reinforce that active care, team integration and skilled support are all non-negotiable elements of dignified behaviour within workplace learning.